Semi‐Egg‐Like Heterogeneous Compartmentalization of Cells Controlled by Contact Angle Hysteresis. (12th June 2015) - Sun, Kang; Liu, Mingjie; Liu, Hongliang; Zhang, Pengchao; Fan, Junbing; Meng, Jingxin; Wang, Shutao
Abstract : Precise control of liquid inside compartments is critically important in bioreactors, combinatorial analysis, and tissue engineering. A contact angle hysteresis (CAH)‐based strategy is demonstrated to construct a semi‐egg‐like hydrogel architecture, leading to spatial heterogeneous compartmentalization of cells. The semi‐egg‐like architecture is fabricated by successively capturing and gelling prehydrogel liquids using a substrate with controlled‐CAH pattern and ultralow‐CAH background. The controlled‐CAH pattern could capture liquid with tunable size, while ultralow‐CAH background prevents liquid sticking. It is envisioned that this CAH‐based strategy would be promising in designing functional surface for engineering complicated architectures of either biomedical or nonbiomedical systems. Abstract : From bad to good: Large contact angle hysteresis (CAH, defined by θ A − θ R ) that causes pinning of droplet on surface is often an unfavorable factor in surface chemistry. It is, however, harnessed in constructing a semi‐egg‐like hydrogel for 3D heterogeneous compartmentalization of cells. By designing surface with controlled‐CAH patterns and ultralow‐CAH background, the semi‐egg‐like architecture is fabricated by dip‐coating in a facile way.